2021
DOI: 10.1186/s12933-021-01265-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of fasting glucose with lifetime risk of incident heart failure: the Lifetime Risk Pooling Project

Abstract: Background Given the rising prevalence of dysglycemia and disparities in heart failure (HF) burden, we determined race- and sex-specific lifetime risk of HF across the spectrum of fasting plasma glucose (FPG). Methods Individual-level data from adults without baseline HF was pooled from 6 population-based cohorts. Modified Kaplan–Meier analysis, Cox models adjusted for the competing risk of death, and Irwin’s restricted mean were used to estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
1
20
0
2
Order By: Relevance
“…Additionally, prediabetic dysglycaemia increases the risk of long-term microvascular and macrovascular complications of diabetes, such as cardiovascular disease and stroke [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, prediabetic dysglycaemia increases the risk of long-term microvascular and macrovascular complications of diabetes, such as cardiovascular disease and stroke [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite prediabetes often being asymptomatic, there is a high risk of progression to type 2 diabetes in those patients [ 5 ]. Additionally, prediabetic dysglycaemia increases the risk of long-term microvascular and macrovascular complications of diabetes, such as cardiovascular disease and stroke [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…levels represent a direct risk factor for cardiovascular diseases, of increasing value from prediabetes to diabetes, to insulin-treated diabetes [5,6]. However, the cardiovascular risk gradually increases with increases in blood pressure regardless of the presence of and of the degree of glucose abnormality [7].…”
Section: Learn More Biomedcentralcom/submissionsmentioning
confidence: 99%
“…In a recently published paper in Cardiovascular Diabetology , Sinha et al [ 7 ] analyzed 40,117 participants from 6 population-based cohorts in the United States. They found that prediabetes (defined as an FPG concentration of 100–125 mg/dL) was associated with a higher lifetime risk of heart failure in middle-aged White adults and Black women, whereas the association was attenuated in older Black women [ 7 ]. This study strongly supports the notion that prediabetes should be regarded not only as a high-risk state for the development of diabetes but also as a risk factor for cardiovascular morbidity.…”
mentioning
confidence: 99%
“…This study strongly supports the notion that prediabetes should be regarded not only as a high-risk state for the development of diabetes but also as a risk factor for cardiovascular morbidity. Interestingly, at almost the same time as publication of the study by Sinha et al [ 7 ], Cai et al [ 8 ] published a meta-analysis showing that the risk of heart failure was higher in individuals with prediabetes than in those with normoglycemia. That meta-analysis included 15 observational studies comprising nearly 10 million individuals with a median follow-up duration of 8.0 years for analysis [ 8 ].…”
mentioning
confidence: 99%